Implementasi Konsep Galeri Pada Interior LKP (Lembaga Kursus Pelatihan) Lelly Tata Rias Pengantin - Rani Hermita; Juli Atika; Muslida Murti (Jurnal Masyarakat Mengabdi Nusantara, 2022)
Along with the development of fashion trends in Medan, people are also starting to get involved in the world of fashion design, both in formal attire and wedding attire. Many wedding fashion designers are still independent in establishing their establishments, such as LKP Lelly. In addition, there are also many designers who sell their services online without having a physical store. Therefore we need a container that can accommodate the work of famous designers so that it is easier to be recognized by the public. Wedding dress designs and accessories vary each year. The designers continue to innovate and produce interesting works from time to time. The bride and groom also need other vendors for the continuity of their marriage, such as vendors for organizers, vendors for pre-wedding photos, and vendors for salons and make-up. For this reason, an area will be provided for several vendors who are competent in their respective fields, making it easier for the bride and groom in their pre-wedding process. With the availability of several facilities in a building at once, it can make it easier for visitors and bride and groom to prepare for their wedding.